MULTIPLE OPPRESSION SUFFERED BY JAVANESE FEMALE CHARACTERS IN OKKY MADASARI’S THE YEARS OF THE VOICELESS - Istiadah, Istiadah; Furaida, Asni; Nabillah, Dwi Rana (Annual International Conferences on Language, Literature, and Media, 2021)
This study analyzes the intersectionality of oppression experienced by Javanese women in the novel The Years of the Voiceless by Okky Mandasari. This study uses Irish Marion Young's oppression theory to explore forms of oppression and Kimberly Crenshaw's intersectionality theory to pay more attention to the existence of oppressions that predominate in women's lives in the new order era. This research found that female characters from three generations named Simbok, Sumarni, Rahayu, Bu Jujuk, and Ndari experience oppression in many ways, including exploitation, powerlessness, cultural imperialism, violence, and marginalization. It intersects with gender, class, state, and society oppression. Suggestions for other researchers are to continue this research by analyzing the agency of women who are also very prominent in the novel, especially Sumarni’s character.